(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to identify social stressors and the coping strategies used to deal with them, as well as to examine their impact on the marital relationship. The study was grounded in the importance of the family as the core unit of society and the various social pressures it faces, which may affect marital stability and the levels of marital satisfaction and adjustment between spouses. The study adopted a descriptive–analytical approach to describe the nature of social stressors experienced by spouses and to analyze the coping strategies employed in مواجهة these stressors. The findings indicated that social stressors represent one of the influential factors affecting the marital relationship, and that the type of coping strategies adopted by spouses contributes either to mitigating the effects of these stressors or to exacerbating them. The study also highlighted the importance of positive coping strategies and social support in enhancing marital stability and improving the quality of the marital relationship. The study recommended raising awareness of effective coping strategies and strengthening the role of marital counseling and social support in assisting spouses to cope with social stressors in a manner that contributes to achieving balance and family stability.